Short Take: Walking Interviews with Refugee-background Women. Issue 3 (August 2021) - Lenette, Caroline; Gardner, Josie
Walking interviews generate contextualized dialogs and place-based narratives prompted by sites and routes. We used walking interviews with three refugee-background women in Australia to find out what the act of walking could reveal about notions of home and broader narratives of forced migration. We used a participatory approach to privilege women's perspectives as co-creators of new knowledge on the topic.